In situ chlorophyll fluorescence kinetics as a tool to quantify effects on photosynthesis in Euphorbia cyparissias by a parasitic infection of the rust fungus Uromyces pisi. (December 2015) - Zhori, Alba; Meco, Marjol; Brandl, Helmut; Bachofen, Reinhard
Abstract Background Photosynthesis is the key process for plant growth and development. The determination of chlorophyll fluorescence kinetics allows the quantification of effects on photosynthetic processes triggered by environmental stress factors such as, e.g., the infection by fungal phytopathogens. The technique is non-invasive, rapid and well suited for experimental field work. Results Healthy andUromyces -infected plants ofEuphorbia cyparissias were monitored directly in situ in the field using rapid fluorescence kinetics. Non-infected healthy plants show a typical maximum value for the relative variable fluorescence Fv /Fm of around 0.8 with occasional variation between the leaves from the plant top towards the base, while infected plants exhibited a strong gradient to low values at the base. The photosynthetic performance index (PI) showed a higher heterogeneity within the leaves in both plant types. Conclusions The non-invasive and rapid measurement of chlorophyll fluorescence induction allows characterizing the photosynthetic capacity of healthy and infected plants and of parts of them directly in the field. The PI, is highly sensitive not only concerning infection, but also towards other local environmental influences.